Past the Parapets of Patriarchy? Women, the Star System, and the Built Environment - Hammond, Cynthia (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
Twenty years after architect Denise Scott Brown challenged the patriarchal exclusion of women from the "star system," what is the status of women in architecture today? Drawing examples from architectural history, recent statistics and current initiatives, the author identifies some of the lingering problems of sexism in architecture, and explores some of the women leaders shaping architectural futures.